A Novel Chaos Application to Observe Performance of Asynchronous Machine Under Chaotic Load - Hakan Öztürk (Chaos Theory and Applications, 2020)
In this study, a novel 4D chaos model is introduced to improve an existing chaotic system. Equations of the chaos model have been written. The dynamical analyses of the system have been executed by means of phase portraits, equilibrium points, eigenvalues, compound structure, and initial conditions. MATLAB/Simulink model has been designed to analyze load which is driven by an induction machine against chaos. Finally, the states of induction machine that is with and without chaotic load is compared.